Resilience of caregivers for pediatric cancer patients: Integrating psychosocial and environmental stressors in the context of occupational and environmental health - Alyanisah, Sadiyyah; Imelda, Johanna Debora (Asian Journal of Toxicology, Environmental, and Occupational Health, 2025)
Background: This study discusses the resilience of parents who care for children with cancer. Without realizing it, parents as caregivers have a crucial role to accompany their children during the treatment process. Furthermore, against the background of psychological and social challenges, parents also endure a decrease in quality of life and disruption of family functioning. Methods: In contrast to previous studies, this study used a literature review method to integrate concepts regarding resilience factors, resilience processes, and resilience functions. In contrast to previous studies, this study used a literature review method to integrate concepts regarding resilience factors, resilience processes, and resilience functions. Based on the inclusion and exclusion criteria, this study reviewed seven previous studies using the case study review method. Findings: There are different types of pediatric cancers and their treatment which leads to differences in resilience factors and processes among parents. These differences in resilience factors and processes resulted in different resilience functions achieved by the parents. Conclusion: Resilience factors are components that contribute to parents' resilience, while resilience functions are outcomes or benefits obtained after parents apply a series of resilience processes. Novelty/Originality of this article: In contrast to previous studies that emphasize individual psychological factors, this study offers a comprehensive perspective by integrating resilience factors, resilience processes, and resilience functions in the context of parents facing childhood cancer.